Cholesterol Inhibition of Isopentenyl Pyrophosphate Δ(3),Δ(2)-Isomerase in Mycoplasma laidlawii - Smith, Paul F. (1970)
Cholesterol inhibits isopentenyl Δ(3),Δ(2)-isomerase of Mycoplasma laidlawii in an apparently competitive fashion. The conversion of mevalonic acid to isopentenyl pyrophosphate is slightly stimulated. Organisms grown in the presence of mevalonic-2-(14)C acid contain small amounts of radio-label in nucleic acid and protein fractions. Most of the label is found in the lipids and is reduced dramatically in organisms grown with cholesterol. No significant accumulation of phosphorylated intermediates of polyterpene biosynthesis was observed in cells or culture supernatant fluid. All of the radioactivity appearing in the nucleic acid fraction occurs in the minor nucleoside, isopentenyl adenosine, of the transfer ribonucleic acid. The necessity for synthesis by the organisms of this minor nucleoside from mevalonic acid may explain the site of enzyme inhibition by cholesterol of polyterpene biosynthesis.